Armies of the Ottoman Empire 1775-1820 - Nicolle, David 1944- (Men-at-arms (Osprey Publishing), 1998)
Covering the period between the reigns of Sultan Selim III and Sultan Mahmut II, this volume details the series of military and naval reforms of the Ottoman armies. It looks at the role of foreign advisors, the impact of the French Revolution and the establishment of military technical schools.